CLINICAL AND BIOLOGICAL STUDY OF RHEUMATOID ARTHRITIS INFLUENCE ON SALIVARY BIOMARKERS ON PATIENTS WITH PERIODONTAL DISEASE - Mãdãlin BOATCÃ; Loredana HURJUI; Ioana RUDNIC; Alexandra MÂRŢU; Ovidiu NICOLAICIUC; Sorina SOLOMON; Silvia MÂRŢU (Romanian Society of Oral Rehabilitation, 2015)
Aim Our purpose was to identify if rheumatoid arthritis (RA) influenced levels of salivary biomarkers of periodontal disease. Methods Biological assessments and periodontal examinations were performed on 15 patients with RA, 10 patients with chronic periodontitis and 11 healthy patients as control group. Unstimulated whole saliva samples were analysed for interleukin-1b (IL-1b) and tumour necrosis factor-α (TNF-α) concentrations. Results The arthritis and healthy groups had significantly less oral disease than the periodontitis group but the arthritis group having significantly moresites bleeding on probing (BOP) than control group. Salivary levels ofIL-1b were significantly elevated in the periodontal disease groupand IL-1b was the only biomarker with significantly higher levels in the arthritis group compared with control group. Arthritis patients receiving anti-TNF-α antibody therapy had significantly lower IL-1b and TNF-α levels compared with arthritis patients not on anti-TNF-α therapy and healthy controls, respectively. Conclusions RA patients have higher levels of periodontal inflammation than healthy control group and also an increased BOP. Systemic inflammation appears to influence levels of select salivary biomarkers of periodontal disease, and anti-TNF-α therapy significantly modify in lowers salivary levels IL-1b and TNF-α levels in RA.